ANALISIS PENGARUH SERVANT LEADERSHIP, DAN PERSONALITY, TERHADAP KINERJA PEGAWAI DENGAN OCB SEBAGAI VARIABEL INTERVENING - anggreini, novi (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to analyze the effect of servant leadership, and personality, on employee performance with organizational citizenship behavior as an intervening variable at the Bantul Regency Health Office. The subjects and objects in this study were all employees at the Bantul Regency Health Office, namely 103 respondents. This type of research uses quantitative techniques and data processing techniques in research using SmartPLS 3.3.3. Servant Leadership has a significant influence on Organizational Citizenship Behavior with a P-Value of 0.021 <0.05. Servant Leadership has no influence and is significant to Employee Performance with a P-Value of 0.462>0.05. Personality has an influence and is significant to Organizational Citizenship Behavior with a P-Value of 0.021 <0.05. Personality has an influence and is significant to Employee Performance with a P-Value of 0.001 <0.05. Organizational Citizenship Behavior has an influence and is significant to Employee Performance with a P-Value of 0.001 <0.05.